Research on the Development and Cultural Ecology of Contemporary Art Book Fair - Fang, Jianjun (Art & Design Research, 2022)
The high development of the Internet and all media has fostered the emergence of the “minority” era. People’s material and spiritual needs have become more and more diversified and personalized. Consumers are no longer a unified whole, but divided into minority groups with common interests or attitudes towards life. It is also under this “minority” demand, Risograph, which was born in 1984, has quietly ushered in a revival. Firstly, through the method of comparative research, this paper analyzes the similarities and differences between risograph perforated printing and the four printing forms, and then systematically combs the historical background and development of risograph printing, discusses its operation principle and minority characteristics, combined with the multi-dimensional drive of social, market and humanistic needs, intuitively observes the artistic ecology of risograph perforated printing and summarizes its artistic effect. Then, through semi-structured interviews and case analysis, take the art printing studio, the main body of printing, as an example to deeply analyze the examples, and use the text analysis method to transform the unstructured original text into structured, highly abstract and characteristic quantitative information, so as to more intuitively reveal its ecological development, operation mode and various problems in the application and promotion of art design, This paper discusses the diversity exploration of cultural activities, the personalized satisfaction of audience groups and the possibility development of visual design, and explores the innovative path of its development and design application.